2017
DOI: 10.1016/j.eurpsy.2016.08.008
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Marketing Campaigns on Reducing Mental Health Stigma: Results From the 2009–2014 Time to Change Programme

Abstract: BackgroundIn England, during 2009–2014 the ‘Time to Change’ anti-stigma programme has included a social marketing campaign (SMC) using mass media channels, social media and social contact events but the efficacy of such approach has not been evaluated yet.MethodsThe target population included people aged between mid-twenties/mid-forties, from middle-income groups. Participants were recruited through an online market research panel, before and after each burst of the campaign (with a mean number of unique parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
94
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(117 citation statements)
references
References 58 publications
7
94
2
Order By: Relevance
“…In England, a large-scale anti-stigma campaign called Time to Change (TTC) has been running since 2007 to reduce mental health-related stigma [24,25]. Over the course of Time to Change, stigma related knowledge, attitudes and desire for social distance have all improved [26,27]. However, some questions have been raised about the effect and appropriateness of anti-stigma programmes [28], because of their implicit or explicit messages about the nature and causes of mental illness.…”
Section: Introductionmentioning
confidence: 99%
“…In England, a large-scale anti-stigma campaign called Time to Change (TTC) has been running since 2007 to reduce mental health-related stigma [24,25]. Over the course of Time to Change, stigma related knowledge, attitudes and desire for social distance have all improved [26,27]. However, some questions have been raised about the effect and appropriateness of anti-stigma programmes [28], because of their implicit or explicit messages about the nature and causes of mental illness.…”
Section: Introductionmentioning
confidence: 99%
“…Thirty-one studies were identified in this review, covering 29 different social marketing programmes, with four articles covering two programmes (Evans-Lacko et al, 2013;Sampogna et al, 2017) and (Tobey and Manore, 2014;Tobey et al, 2016) (see Table 2). The majority of the identified programmes were conducted in developed countries, including the United States (n=17), Canada (n=2), Australia (n=2), the United Kingdom (n=2), and other European countries (n=2).…”
Section: Programme Overviewmentioning
confidence: 99%
“…Next to the well-known and often replicated finding that familiarity with mental illness or mentally ill people lowers public stigma on an individual level (e.g. Corrigan 2004Corrigan , 2012Corrigan et al 2012 andSchomerus et al 2007), limited research considers relevant personality traits as potential moderators in anti-stigma campaigns though, despite some evidence of their effects (Sampogna et al 2017). Public stigma, as we define it, implies discriminatory attitudes among a general population toward a certain group of individuals, which lead to increased distance.…”
Section: Implicit Worldviews As Antecedents Of Public Stigmamentioning
confidence: 99%
“…et al (2013) /Sampogna et al (2017) Social contact with individuals with mental health problems is an effective anti-stigma social marketing programFrosch et al (2008) Patient lay beliefs about a disease label (e.g., hypertension vs. Korotkoff's Syndrome) affect treatment preferences with "realistic" body types reduces self-stigma and subsequently lowers motivation to engage in healthy behaviorsLincoln et al (2008) Biomedical public anti-stigma campaigns are more effective for medical students, whereas biopsychosocial campaigns are more effective for reducing mental health stigma with psychology students Greater health motivation, health knowledge, health locus of control, behavioral control and education, income and youth are related to greater likelihood of consumers engaging in preventative health behaviors. (2007) Antismoking public service announcements are most effective when framed to fit an individual's regulatory orientation; positively framed ads fit with a promotion focus, and negatively framed ads fit with a prevention focus.…”
mentioning
confidence: 97%